2016
DOI: 10.1002/ece3.2538
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in nematode diversity and ecological roles along the Chinese coast

Abstract: AimTo test changes in the phylogenetic relatedness, niche breadth, and life‐history strategies of nematodes along a latitudinal gradient.LocationSixteen wetland locations along the Pacific coast of China, from 20°N to 40°N.MethodsLinear regression was used to relate nematode phylogenetic relatedness (average taxonomic distinctness (AvTD) and average phylogenetic diversity [AvPD]), life‐history group (based on “c‐p” colonizer–persister group classification), and dietary specificity (based on guild classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
8
22
0
Order By: Relevance
“…In our study, for native P. australis community, soils with high moisture content and low pH tended to have bacterial dominated microbial communities and high B:F ratios, and this is consistent with other studies , Zhou et al 2017. In native communities, composition of soil communities at continental and global scales should reflect geographic variation in abiotic condition, soil types, and other dominant species that influence the soil community, resulting in high beta diversity at geographic scales (Wu et al 2016, Price et al 2018, Ren et al 2018. Thus, for both nematodes and soil microbial communities, the geographic variation found in native communities was absent, homogenized, in stands of the exotic plant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, for native P. australis community, soils with high moisture content and low pH tended to have bacterial dominated microbial communities and high B:F ratios, and this is consistent with other studies , Zhou et al 2017. In native communities, composition of soil communities at continental and global scales should reflect geographic variation in abiotic condition, soil types, and other dominant species that influence the soil community, resulting in high beta diversity at geographic scales (Wu et al 2016, Price et al 2018, Ren et al 2018. Thus, for both nematodes and soil microbial communities, the geographic variation found in native communities was absent, homogenized, in stands of the exotic plant.…”
Section: Discussionsupporting
confidence: 90%
“…The geographic pattern that we found for these life-history groups is consistent with previous latitudinal studies in coastal habitats in China (Wu et al 2016). Within stands of P. australis, plant and algal feeders varied in relative abundance across latitude, and all three life-history groups also varied in relative abundance across latitude.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…drives diversity patterns of a broad range of taxa (Mittelbach et al, 2007; Schluter & Pennell, 2017). In addition to climatic parameters, however, other studies have emphasized the importance of edaphic parameters and plant traits in driving patterns of soil nematode richness and diversity (Fonseca & Netto, 2015; Sauvadet, Chauvat, Fanin, Coulibaly, & Bertrand, 2016; Wu et al, 2016). In this study, edaphic parameters were not related to soil nematode richness and diversity in the native range of S. alterniflora (Appendix : Figures –S6).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a meta‐analysis, Song et al (2017) found that the diversity of nematodes was positively correlated with annual mean temperature. Likewise, Wu et al (2016) found that climatic variables including annual temperature range and edaphic variables like pH were very important in influencing nematode community structure in coastal wetlands dominated by native plants. Because soil nematodes may respond to fine‐scale changes in soil resources, pH and moisture, they interact with environmental parameters at fine spatial scales, and these interactions and processes may be important in determining diversity patterns (Neher, 2010).…”
Section: Introductionmentioning
confidence: 98%